Legal Protection of Muzakki in Zakat Crowdfunding: Analysis of Maqasid Asy-Syari'ah - Fad, Mohammad Farid; Imron, Ali (UIN Sunan Kalijaga, 2021)
Abstract: The concept of crowdfunding is rooted in the concept of crowdsourcing. It utilizes a